PERLINDUNGAN HUKUM TERHADAP WHISTLEBLOWER DAN JUSTICE COLLABORATOR DALAM UPAYA PEMBERANTASAN TINDAK PIDANA KORUPSI - Nixson Nixson; Syafruddin Kalo; Tan Kamello; Mahmud Mulyadi (USU LAW JOURNAL, 2013)
The development of the modus of corruption criminal act in Indonesia today has indicated a wide scale and become more sophisticated so that it is very difficult to prove it. One of the methods to uncover this organized crime of corruption is by using the role of whistleblowers that can help uncover the modus of corruption criminal act more easily. Unfortunately, whistleblowers and justice collaborators in corruption case in Indonesia have not received maximal legal protection; in consequence, people who want to expose the crime and who have the right to gain reward will go to prison instead. In Indonesia, judicial normatively, based on Law No.13/2006, whistleblowers and justice collaborators have not yet received maximal legal protection. The same is true for SEMA No.4/2011; whistleblowers and justice collaborators only received leniency of a sentence. The ideal legal protection is by giving reward, treatment, and protection from all charges as the compensation for what a whistleblower has exposed, whether he is one of the perpetrators or not. Keywords : Legal Protection, Whistleblowers, Justice Collaborator